TANK shapes an immunosuppressive microenvironment and predicts prognosis and therapeutic response in glioma - Li, Shasha; Guo, Youwei; Hu, Huijuan; Gao, Na; Yan, Xuejun; Zhou, Quanwei; Liu, Hui (Frontiers in Immunology, 2023)
Background： It is unknown whether TANK plays a role in gliomas, which are immunologically heterogeneous. Methods： TANK mRNA expression patterns were assessed from public databases, and qPCR and IHC in an in-house cohort were performed to confirm the clinical significance of TANK. Then we systematically evaluated relationship between TANK expression and immune characteristics in the glioma microenvironment. Additionally, we evaluated TANK’s ability to predict glioma treatment response. TANK-associated risk scores were developed to test their prognostic abilities. Results: TANK was specifically overexpressed in glioma, and enriched in the malignant phenotype, which was related to poor prognosis. A tumor microenvironment that is immunosuppressive was evident by the negative correlation between TANK and immunomodulators, cancer immunity cycles, and immune checkpoints. Notably, treatment for cancer may be more effective when immunotherapy is combined with anti-TANK therapy. Prognosis could be accurately predicted by the risk score. Conclusions: As well as predicting prognosis, TANK can also predict responses to several treatments.